Поліморфізм високомолекулярних субодиниць глютенінів Aegilops biuncialis vis. - Козуб, Н.О.; Созінов, І.О.; Бідник, Г.Я.; Дем’янова, Н.О.; Ксиніас, І.; Блюм, Я.Б.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2015)
Aims. Polymorphism of high-molecular-weight glutenin subunits (HMW-GS) encoded by the Glu-U1, Glu-Mb 1 loci was analyzed in Aegilops biuncialis mainly from Crimean populations. Methods. SDS electrophoresis of total seed protein was used to identify alleles at the Glu-U1 and Glu-Mb 1 loci. Results. Among the samples studied, 10 alleles at Glu-U1 and 18 at Glu-M1 were identified. Among them 2 alleles expressed only x-type subunit and 5 expressed only y-type subunit. Nei’s gene diversity was 0.683 і 0.723, respectively, for these loci. Predominant alleles and subunits of each type were determined. Conclusions. A high level of polymorphism of HMW-GS in Ae. biuncialis permits using these loci for investigation of the genetic structure of populations, their monitoring and studying dispersal of the species. Keywords: Aegilops biuncialis, diversity, high-molecular-weight glutenin subunits, alleles.